Numerical study on retrofitting opposed firing boilers with a slag-tap combustion chamber - Wu, Qinglong; Fang, Fan; Guan, Jingyu; Zhu, Lingkun; Chen, Yang; Deng, Lei (Frontiers in Energy Research, 2025)
The utilization of high-alkali coals like Naomaohu coal in conventional opposed firing boilers faces operational challenges due to severe slagging and fouling caused by low ash fusion temperatures and elevated sodium content. This study proposes a cost-effective retrofit design integrating a slag-tap combustion chamber with modular airflow control, preserving the original slag discharge mechanisms of a 350 MW supercritical opposed firing boiler. Three-dimensional numerical modeling based on the Computational Fluid Dynamics (CFD) simulations is conducted to evaluate the flow field, thermal, and gas-phase composi-tional distributions across the Naomaohu coal combustion ratios (20%, 25%, and 30%). The retrofitted configuration enhances slag capture efficiency and reduces fouling risks while maintaining combustion stability. Results demonstrate that elevated combustion ratios intensified the momentum of exhaust jets originating from the slag-tap combustion chamber, generating pronounced flow perturbations within the furnace volume. At the 30% combustion ratio, the jet extends its penetration distance, redistributing pulverized coal particles toward the furnace center and creating distinct thermal zones, including a high-temperature core (∼2140 K) and peripheral low-temperature regions (∼1600 K). Oxygen depletion in the upper-middle furnace correlates with intensified combustion reactions, while CO2 accumulation reflects enhanced gas-phase reaction completeness. This study provides critical insights into optimizing combustion systems for high-alkali coals, balancing operational reliability with sustainable energy generation.